2013
DOI: 10.1038/npp.2013.190
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of GABAA Receptor Subunits is Altered in Schizophrenia

Abstract: The molecular mechanisms of schizophrenia have been under investigation for decades; however, the exact causes of this debilitating neuropsychiatric disorder are still unknown. Previous studies have identified multiple affected neurotransmitter systems, brain regions, and cell types, each making a unique contribution to symptom presentation and pathophysiology. Numerous studies have identified gene and protein expression changes in schizophrenia, but the role of post-translational modifications, specifically N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 42 publications
4
68
1
Order By: Relevance
“…In the superior temporal gyrus, altered N-glycosylation of GABAA receptor has been shown in schizophrenia [7]. In our study, it should be noticed that lectin-positive SPD in the molecular layer of dentate gyrus of hippocampal formation in patients with schizophrenia is observed also in drug naïve cases, though some experimental studies showed that a kind of therapeutic products of major tranquillizers induced neuron apoptosis in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 44%
“…In the superior temporal gyrus, altered N-glycosylation of GABAA receptor has been shown in schizophrenia [7]. In our study, it should be noticed that lectin-positive SPD in the molecular layer of dentate gyrus of hippocampal formation in patients with schizophrenia is observed also in drug naïve cases, though some experimental studies showed that a kind of therapeutic products of major tranquillizers induced neuron apoptosis in the dentate gyrus.…”
Section: Discussionsupporting
confidence: 44%
“…If this process is disrupted, decreased 26S proteasome activity may result in the retention of misfolded proteins and/or abnormal incorporation of neurotransmitter receptor subunits into complexes that are then trafficked to the synapse. This may be a contributing factor to the abnormal N-glycosylation and subcellular localization of both glutamate and GABA receptor subunits that we have previously reported in schizophrenia (Hammond et al, 2010;Tucholski et al, 2013a, b;Mueller et al, 2014Mueller et al, , 2015. Degradation of proteins can be accomplished by several proteasome types other than the 26S, including uncapped 20S CP, the IP, and 11S γ RP-capped proteasomes.…”
Section: Discussionmentioning
confidence: 71%
“…Glycosylation, ubiquitination, myristoylation, and phosphorylation are some of the PTMs that have recently been studied in schizophrenia brain (Bauer et al, 2010; Mueller et al, 2014; Pinner et al, 2014; Rubio et al, 2013; Tucholski et al, 2013a; Tucholski et al, 2013b). …”
Section: 0 Introductionmentioning
confidence: 99%
“…Recent studies in postmortem cortex in schizophrenia have found alterations of N-linked glycosylation of the ionotropic glutamate receptor subunits GluA2 and GluK2, glutamate transporters EAAT1 and EAAT2, and γ-aminobutyric acid (GABA) A receptor subunits α1, β1, and β2 (Bauer et al, 2010; Mueller et al, 2014; Tucholski et al, 2013a; Tucholski et al, 2013b). In addition, abnormal expression of glycan structures in cerebrospinal fluid (CSF) and serum (Stanta et al, 2010), abnormal expression of sphingolipid metabolism genes (Kittler et al, 2002), and dysregulated cytoplasmic chondroitin sulfate proteoglycan expression (Macdonald et al, 2009) have all been reported in schizophrenia.…”
Section: 0 Introductionmentioning
confidence: 99%